(untitled) (Journal of Nobel Medical College, 2012)
Background: The symptoms of anxiety are widely prevalent among the former opioid addicts in methadone maintenance treatment (MMT). It is clinically important to be aware of the severity of the co-morbidity as it plays a crucial role in the methadone dosage, length of time in treatment and the relapse rate and the co-existence of co-morbidity has been described as the factor which worsens the prognosis. Aim: to study the prevalence of the symptoms of anxiety among MMT clients Methods: a descriptive, survey and a cross- sectional study, 60 MMT clients were selected who had been attending the MMTP for more than 2 months and were given with semistructured proforma specifically designed for this study only. Then after, they were evaluated for the anxiety symptoms with Beck Anxiety Inventory (BAI). Finally, the information obtained from the demographic profile and the rating scale were analyzed with the help of computer program SPSS. Results: The study showed around 41.7 % of the patients had symptoms of anxiety with varying severity. Correlates of presence of anxiety symptom among MMT client in the present study showed higher prevalence among age group 20-29(88%), 66% were separated and 64% were unmarried, 50% were Buddhist, majority of the case were chhetri (70%), 75% had primary level education, 67% were unemployed, and 65% from middle class socioeconomic status. Limitation: The study was a cross sectional, which showed only the symptoms of anxiety not the disorder and the drug use, withdrawals itself, could distort evaluation and lead to misdiagnosis of anxiety. Conclusion: The major risk factor for was male gender, separated, primary education level, students and middle socio-economic status. DOI: http://dx.doi.org/10.3126/jonmc.v1i1.7283 Journal of Nobel Medical College Vol.1(1) 2011 15-19